Analisis Sektor Ekonomi Unggulan dalam Pengembangan Potensi Perekonomian di Kabupaten Kepulauan Meranti - Reni Muhertenti; Dahlan Tampubolon; Mardiana (Jurnal Multidisiplin Madani, 2022)
The purpose of this study is to determine the leading economic sector and the value of the income multiplier effect, shifting economic structure in Meranti Islands Regency. This type of research is descriptive quantitative. The data used secondary data is time series data obtained from BPS. The analytical tools used are Location Quotient (LQ) and shift share. The results of the LQ analysis show that the leading sectors are agriculture, forestry and fisheries, the transportation and warehousing sector, the government administration sector, defense and mandatory social security. The results of the shift share analysis that are included in the competitive advantage are agriculture, forestry and fisheries. From the results of the analysis using two tools, namely LQ and shift share, which are included in the leading economic sectors in the Meranti Islands Regency, namely: the agricultural, forestry, and fishery sectors. These sectors include basic and competitive sectors.